Outcomes associated with total neoadjuvant therapy with non-operative intent for rectal adenocarcinoma - Asare, Ebenezer; Venner, Emily; Batchelor, Hanna; Sanders, Jason; Kunk, Paul; Hedrick, Traci; Hoang, Sook; Reilley, Matthew; Le, Tri; Friel, Charles; Janowski, Einsley-Marie (Frontiers in Oncology, 2024)
Purpose/objective(s) To evaluate rates of clinical complete response (cCR), surgery-free survival, permanent ostomy-free survival, and factors associated with these outcomes in patients treated with total neoadjuvant therapy (TNT) with intent for non-operative management of rectal adenocarcinoma. Methods A retrospective review was conducted of patients treated with TNT for stage II-IV rectal adenocarcinoma (n=45) at our institution between 2013 – 2022 with curative intent. All patients received radiation with concurrent capecitabine and additional chemotherapy, either prior to or following chemoradiation (CRT), with intent for non-operative management. Response rates were determined based on post-treatment MRI and endoscopy. Kaplan-Meier method was utilized to estimate the 1- and 2-year surgery- and permanent ostomy-free survivals. Cox regression was used to evaluate associations between surgery- and permanent ostomy-free survivals and various factors of interest, including patient and tumor characteristics and clinical response. Chi-squared analysis compared rates of cCR and surgery by sequence of TNT modality and cell count ratios. Results Of the 45 patients treated with TNT, most patients had low-lying rectal tumors with a median distance of 4.1 cm from the anal verge (range, 0.0 – 12.0). Overall, 64.4% (n=29) achieved cCR after TNT. 13 patients (28.9%) underwent surgical resection following TNT, 12 of whom had incomplete response and one who elected to undergo surgery after reaching cCR. At median follow up of 32.0 months (range, 7.1 – 86.1), 22.2% (n=10) of patients had a permanent colostomy, with only 2 of these completed for tumor regrowth after cCR. At one and two years, respectively, surgery-free survival was 77.3% and 66.2%, and permanent ostomy-free survival was 90.9% and 78.2%. Rates of cCR were higher in patients who received CRT first compared to those who received chemotherapy first (72.2% vs. 33.3%, p=0.029) and rates of surgery were also lower in patients who received CRT first compared to those who received chemotherapy first (19.4% vs. 66.7%, p=0.005). On Cox regression model, cCR on 6 month post-CRT endoscopy was associated with surgery-free survival (p=0.006) and permanent ostomy-free survival (p=0.033). Clinical response at earlier follow up points did not predict surgery- nor permanent ostomy-free survival. Conclusion These results support evidence that TNT may be a non-surgical option for select patients with rectal adenocarcinoma who desire organ preservation. In this investigation at a single institution, the treatment response on 6-month post-CRT endoscopy was the best predictor of surgery- and permanent ostomy-free survival, which are outcomes that are important to patient quality of life. CRT followed by consolidation chemotherapy was associated with higher rates of cCR and lower rates of surgery compared to those treated with induction chemotherapy.